Competition and segmentation : an analysis of wage determination and labour adjustments in manufacturing industry - McCartan, Patrick John (Rhodes University, Faculty of Commerce, Department of Economics, 1986)
The thesis itself proceeds according to the following outline. Chapter One is concerned with the neoclassical theory of the labour market. Three particular models are surveyed all of which attempt to explain wage differentials and labour adjustments within a competitive equilibrium framework. The basic model of the labour market which rests upon the marginal productivity theory of labour demand, the utility-maximising approach to labour supply and the competitive theory of market equilibrium is dealt with first.This is followed by an outline of human capital theory which emphasises the crucial role played by education and training in determining individual earnings . Finally, attention is focused on disequilibrium wage models of adjustment which account for wage dispersion in terms of the amount and quality of information available to transactors in the labour market.(Introduction, p. 3-4)
Keywords: Labour supply; Labour market; Competition -- South Africa